Cuppa Convo with Marni: confidence through casual English conversations / Marni Jamil - Jamil, Marni (Academy of Language Studies, 2024)
The Cuppa Convo with Marni: Confidence through Casual English Conversations (Cuppa Convo) programme was an initiative spearheaded by Ms. Marni Jamil, an English lecturer from the Academy of Language Studies at Universiti Teknologi MARA Pulau Pinang Branch (UiTMCPP), aimed at sharing her expertise with the university community. This programme was initiated in response to requests from UiTMCPP staff who expressed interest in participating in English language lessons but faced challenges committing to long-term engagements. Cuppa Convo, comprising three sessions on 18th, 19th, and 26th January 2024 from 4.00 pm to 5.00 pm at the Perpustakaan Tun Abdul Razak Library (PTAR) UiTMCPP offered the university personnel a consistent opportunity to practise English. The primary aim of the programme was to foster English communication among UiTMCPP staff, while bolstering their confidence in expressing ideas and communicating effectively in English within a relaxed environment. The distinctive aspect of the concept was its departure from formal learning approaches. It embraced casual conversations ("Convo") and a relaxed atmosphere, akin to enjoying coffee ("Cuppa"), effectively aligning with its objectives. Proficiency in English communication is important for UiTM staff, particularly in the context of UiTM's 2025 Strategic Plan, aimed at positioning the university as a globally recognised institution. Essentially, English serves as a medium for knowledge dissemination and facilitates the exchange of experiences and the cultivation of robust interpersonal relationships across diverse backgrounds.